Effects of Tiletamine-Zolazepam and Isoflurane for Induction and Maintenance in Xylazine Premedicated Dogs - Anjana, Ruchikkumar R.; Parikh, Pinesh V.; Kelawala, Divyesh N. (Indian Journal of Veterinary Sciences and Biotechnology, 2021)
This study was aimed to evaluate the quality of induction and recovery from anesthesia promoted by the tiletamine-zolazepam and  isoflurane for induction and maintenance with xylazine premedication in dogs. For this, clinical cases of six dogs were selected randomly.  Animals were premedicated with atropine sulphate (0.04 mg/kg, i/m) and xylazine (0.5 mg/kg, i/m). Anesthesia was induced with a  combination of tiletamine-zolazepam (2 mg/kg, i/v) and maintained by isoflurane (1.5-2.5%). Different physiological parameters, viz.,  rectal temperature (°C), heart rate (beats/min), respiratory rate (breaths/min), and SpO2 (%), were recorded at every 10 minutes. The  quality of anesthesia was assessed based on analgesia, muscle relaxation, body reflexes, quality of induction & recovery. The quality of  induction and recovery was smooth and safe. No complications were encountered in animals indicating that the anesthetic protocol  employed was safe and effective for surgical procedures.
Keywords: Anesthesia; Dog; Isoflurane; Tiletamine-zolazepam; Xylazine